Identification of missed hypertension and hypertensive arteriopathy with home versus ambulatory blood pressure measurement in patients with tia or minor stroke. - Webb, A; Li, L; Simoni, M; Wilson, M; Paul, N; Tarassenko, L; Rothwell, P (2013)
Hypertension is a major treatable cause of incident and recurrent stroke. However, it can be missed by one-off clinic measurements. Hypertension guidelines therefore currently recommend ambulatory monitoring (ABPM) prior to treatment in primary prevention. Given high rates of under-treatment of hypertension in secondary prevention after TIA and stroke, we compared Bluetooth home BP monitoring (HBPM) and ABPM in identifying hypertension missed at initial assessment, with validation against pre-morbid BP and markers of hypertensive arteriopathy.